Decomposition analysis of global value chains: Uncovering vulnerable spots in a selected economy (the example of Czechia) - Kuzmenko, Elena; Čechura, Lukáš (Heliyon, 2023)
Recent global turmoil has added to the importance of food security issues and the sustainability of production processes worldwide. This study aims to uncover the degree of domestic industries' dependence on the international fragmentation of production processes and identify the countries of origin of those producers who have managed to displace domestic producers in corresponding Global Value Chains. Using data retrieved from the World Input-Output Database, we studied Czechia's example via demarcation of domestic value-added (DVA) shares from foreign ones in final domestic products. A declining trend in DVA signalises an ever-increasing dependence on foreign inputs. The conducted analysis allowed a VA-structure (and its dynamics for a sequence of years) to be clearly identified for final domestic products among 30 industries that virtually cover the entire economy. The most alarming finding is the marked reduction of DVA in food manufacturing, which points to a weakening of Czech food security. Realising all the connections within GVCs may help to identify vulnerable spots in domestic production processes and prepare adequate response mechanisms in potential situations of possible interruptions from the foreign side. The detailed explanation of the decomposition technique provided in the study can be used in similar analyses of other economies to reveal noteworthy trends and prepare response measures.
Keywords: Food security; Input-output analysis; Global value chains; Czechia; Value-added; Final domestic product